Indicadores de sustentabilidad en fincas ganaderas productoras de leche en la parroquia Valle Hermoso, cantón Santo Domingo - López Vera, Mishell Angélica (2022)
Five productive systems based on dairy farming were characterized in the Valle Hermoso parish, Santo Domingo canton, whose objective was to define the indicators of ecological, economic and sociocultural sustainability for this type of production. The information was obtained through face-to-face surveys and on-site visits to five cattle farms (cases). For their selection, the willingness of the producers towards the study was taken into account, as well as the existence of dairy cattle in the production system. The study was observational, descriptive and exploratory using the case study as a strategy. Indicators of economic, ecological and sociocultural sustainability will be applied, for which an indicator evaluation mechanism will be established following the Sarandon methodology